Prevalence and Factors associated with Helicobacter pylori among Adults between 18 and 40 Years at Butembe Health Centre III Kyankwanzi district, Uganda. - Kakooza, Shubeika (Student’s Journal of Health Research Africa, 2021)
Background: The prevalence of Helicobacter pylori infection varies by geography, ethnicity, and socioeconomic factors. Available data on the prevalence of Helicobacter pylori infection in Uganda are not representative of the general population. We sought to describe the prevalence and factors associated with H.pylori among adults between 18 and 40 years at Butemba Health Centre III. Methodology: Using a cross-sectional design, H. pylori infection was assessed by the H.pylori antibody test among 181respondents attending Butemba Health Centre III in Kyankwanzi. Data were collected by face-to-face interviews using a questionnaire. Associations between H. pylori infection and factors associated were analyzed using logistic regression. Results: The overall prevalence of H. pylori infection was 29.2%. However, H. pylori infection was highest (54.14%) in the age of 18 to 30 years study participants followed by 31 to 40 years (45.8%). H. pylori was associated with smoking of cigarettes (AOR = 0.732; 95% CI: 0.275-1.950), drinking alcohol (AOR = 4.373; 95% CI: 1.359-14.06), Poor sanitation (AOR = 5.33; 95% CI: 2.556-11.11) were also independently associated with H. pylori infection. Conclusion and recommendation: The prevalence of H. pylori infection in Kyakwanzi at 29.2% calls for population-based studies in the region and offers an opportunity to study the transmission dynamics of H. pylori infection. Changes in public health measures need to be instituted in the management of H. pylori infection to include education of the population and health care workers on the non-specific and insidious clinical presentation of the condition.